Art and Archaeology in Ancient Rome - Soren, David; Martin, Archer (Midnight Marquee Press, Inc., 2015)
"This book will layout the basic information and steps necessary to take the beginning archaeologist's search for knowledge of the past and lead them to adventures of the future."-- Provided by publisher
"A Publication of the Joseph and Mary Cacioppo Foundation."
Keywords: Rome -- Antiquities.; Art, Roman.; Rome -- Antiquités.; Art romain.; Antiquities; Art, Roman; Rome (Empire)